Fostering Soft Skills in Active Labor Market Programs: Evidence from a Large-Scale RCT - Analia Schlosser; Yannay Shanan (Institute of Labor Economics (IZA), 2022)
The long-term unemployed sometimes lack basic soft skills needed to enter and succeed in the labor market. We examine whether it is possible to develop or enhance these skills among adults by using a large-scale randomized control trial (RCT) to evaluate the effectiveness of an Active Labor Market Program (ALMP) that targets income-support claimants in Israel. In this program, participants receive personalized treatment composed of weekly sessions with occupational trainers and motivational group workshops. We find that the program increased participants' employment rate by 8 percentage points (a 24% increase) and decreased income support recipiency by 11 percentage points (a 26% decline) relative to the control group. The effects are larger among individuals with a lower attachment to the labor market and lower likelihood of employment such as high-school dropouts and those with a longer history of welfare dependence. Income from work increased both for treated individuals and for their untreated spouses suggesting that the program had positive spillovers within the household. There is no evidence of displacement effects on the control group. The analysis of the mechanisms at work shows that the program had positive and significant effects on participants' soft skills, mainly among those with no recent employment spell, who gradually joined the labor market after participation in the program. In contrast, it induced individuals who had a recent employment spell to go back to employment soon after their allocation to the program. The program effects persist in the long run, even during the Covid-19 crisis, about five to six years after its implementation. We conclude that unemployed income-support claimants with no recent employment spells can benefit considerably from interventions that aim to improve their soft skills.
Keywords: J24; J64; 330; ALMP; program evaluation; soft skills; non-cognitive skills